Kelas Ibu Hamil untuk Meningkatkan Kesejahteraan Ibu dan Janin di Posyandu - Hilda Prajayanti; Swasti Artanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2022)
Pregnant Women Class is a study group for pregnant women with a gestational age of between 4 weeks and 36 weeks (before delivery). Pregnancy is one of the stages of life that must be prepared by a woman, in the process of pregnancy physiological and psychological changes occur due to an increase in estrogen and progesterone. The risk factors for maternal death during childbirth began from under-monitored pregnancy. One of the efforts to reduce maternal mortality is through classes for pregnant women. This class for pregnant women is a means to learn together about health for pregnant women, in the form of face-to-face in groups that aims to increase the knowledge and skills of mothers regarding pregnancy, pregnancy care, childbirth, postpartum care, newborn care, myths, diseases. infection and birth certificates. The objectives of implementing this community service are: Increasing interaction and sharing experiences between participants (pregnant women and pregnant women) and between pregnant women and health workers/midwives, Increasing understanding, attitudes and behavior of pregnant women about classes for pregnant women, body changes and complaints, treatment pregnancy and preparation for delivery. To be able to improve the knowledge and skills of mothers regarding pregnancy, pregnancy care, childbirth, community service can be carried out in the form of maternal and child health counseling that can be carried out through pregnant women classes. From the results of the activity, it can be concluded that the activity went smoothly, the participants were enthusiastic in participating in the counseling and question and answer session and were active in doing pregnancy exercise, most of the participants said they felt relaxed and excited after participating in the pregnancy exercise and were also ready to wait for the delivery process.